Pengaruh Majalah Biosistem Pada Materi Sistem Peredaran Darah Terhadap Hasil Belajar IPA Peserta Didik Kelas VIII SMP: (The Effect of Biosystem Magazine on Students Learning Outcomes in Science Regarding the Circulatory System Material Among VIII Grade Students at Junior High School) - Inayah Ibnu Nasir , Putri Ainun; Titin , Titin; Yeni , Laili Fiti (BIODIK, 2025)
The purpose of this study was to analyze the effect of biosystem magazine on the circulatory system on student learning outcomes at SMP Negeri 2 Pemangkat. This study used a quasi-experimental design method with a pretest-posttest control group design. The sample of this study was class VIII C (experimental class) and class VIII D (control class) determined by purposive sampling technique. This study used learning outcome test instruments, RPP and LKPD with validation and reliability test criteria stating valid and reliable. Based on the results of the study, the effect on student learning outcomes analyzed using normality and homogeneity tests, it was obtained that the experimental class had a significance value> 0.05, thus the experimental class learning outcomes were normally distributed and homogeneous. In the independent sample t test, the experimental class had a significance value <0.05, meaning that Ho was rejected and Ha was accepted, it was concluded that there was an effect on student learning outcomes in the experimental class using biosystem magazine. Abstrak. Tujuan penelitian ini untuk menganalisis pengaruh majalah biosistem pada sistem peredaran darah terhadap hasil belajar siswa di SMP Negeri 2 Pemangkat. Penelitian ini menggunakan metode quasi experiment design dengan rancangan pretest-posttest control group design. Sampel penelitian ini yaitu kelas VIII C (kelas eksperimen) dan kelas VIII D (kelas kontrol) ditentukan dengan teknik purposive sampling. Penelitian ini menggunakan instrumen tes hasil belajar, RPP dan LKPD dengan kriteria hasil validasi dan uji reliabilitas meyatakan valid dan reliabel. Berdasarkan hasil penelitian pengaruh hasil belajar siswa yang dianalisis menggunakan uji normalitas dan uji homogenitas, diperoleh kelas eksperimen memiliki nilai signifikansi > 0,05 dengan demikian hasil belajar kelas eksperimen berdistribusi normal dan bersifat homogen. Pada uji independent sample t test, diperoleh kelas eksperimen memiliki  nilai signifikansi < 0,05 artinya Ho ditolak dan Ha diterima, disimpulkan bahwa terdapat pengaruh hasil belajar siswa pada kelas eksperimen menggunakan majalah biosistem.